Pemilihan Pembiayaan KPR (Kredit Pemilikan Rumah) Dengan Akad Murabahah (Studi kasus di Bank Muamalat Tbk Cabang Pembantu Samarinda Seberang) - Sapi'i Sapi'i; Agus Setiawan (Al-Tijary, 2016)
Having your own home is the dream of all people, even being the basic human needs that must be met. But most people cannot afford to buy with cash to buy in installments or credit and the bank Muamalat itself, provided a variety of KPRS that can be selected according to the needs and interest free. Having your own home is no longer a difficult one, because there are the housing loans granted by banks commonly called mortgage (KPR). Bank Muamalat was present meet the demand of people with the name Residential Syariah financing from Bank Muamalat is a financing facility for residential property in accordance with Islamic principles. Thatneeds with of the community in the ownership of the house in installment and in accordance with Islamic principles. The purpose of this study to determine Factors Influencing the Customer in choosing a mortgage with AkadMurabaha Financing. This study concluded that the factors Customers Choose AkadMurabaha Financing mortgages with Religion is a factor, Factor Location Factor, Friends, Ad Factors, Economic Factors, Care Factor.